HUBUNGAN KEMANDIRIAN DENGAN KEMAMPUAN TEKNIS BEKERJA PEMUDA TANI PEDESAAN - Muksin Muksin; Amri Jahi; Margono Slamet; Djoko Susanto (Jurnal Penyuluhan, 2008)
This research objectives are: (1) to describe characteristics of work autonomy of the farmer youth, (2) to describe technical ability of work, and (3) to analyze relation of work autonomy and technical ability of work. The technique of data collection is using cluster sampling. The number respondent are 251 of youths. The data analysis used descreptive and Chi square analysis. The research results were: The technical ability of farmer youth are lower than youth group that have non agricultural’s job. There are importance to develop Farmer youth technical ability with sistematically process, facilitation and support from the government. Hence, it is suggested to have sound planning and action in agricultural extension program to motivate and enhance the farmer’s youth to get involve in agricultural activities development.